Phytoliths in Inflorescence Bracts: Preliminary Results of an Investigation on Common Panicoideae Plants in China - Ge, Yong; Lu, Houyuan; Zhang, Jianping; Wang, Can; Gao, Xing (Frontiers in Plant Science, 2020)
Phytoliths in the inflorescence of Poaceae plants can be of high taxonomic value in some archaeological contexts and provide insight into plant taxonomy and crop domestication processes. In this study, phytoliths in every inflorescence bract of 38 common Panicoideae weeds and minor crops in China were studied. Based on dissection of the inflorescence into different bracts using a treatment that retained the phytoliths anatomical position, observations of inflorescence phytoliths types and distribution were described in detail. We found that INTERDIGITATING, BLOCKY AMOEBOID, RECTANGULAR DENTATE, and ELONGATE DENDRITIC with multi tent-like arch tops were of higher taxonomic value than the other types in our studied species. Both morphological and morphometric traits of the INTERDIGITATING were summarized and compared with previous studies; the findings suggested that genus level discrimination of some Paniceae species could be reliable, and tribe/species level discrimination might be feasible. The phytoliths in the involucre of domesticated and wild type Coix lacryma-jobi provided insight into the domestication process of this plant. Our data also indicated that phytolith production in the inflorescence bracts might be under the genetic and molecular control of inflorescence development. Thus, the findings of this study could assist future studies in plant taxonomy and archaeobotany.